Primary Small Cell Neuroendocrine Carcinoma of the Mediastinum: Case Report of a Rare Entity - Zanellato, Magno Giovani; Ojopi, Elida Paula Benquique; Souza, Daniela Cristina dos Santos (Brazilian Journal of Case Reports, 2025)
Small neuroendocrine carcinoma of the mediastinum (SCNCM) is a rare subtype of neuroendocrine malignancy characterized by its aggressive behavior and high rates of recurrence and metastasis. The diagnosis of this carcinoma is challenging, requiring confirmation through histopathological and immunohistochemical analysis, as well as specific imaging studies. This study reports a case of primary SCNCM that resulted in the death of a 59-year-old female patient treated at the Clinical Hospital, School of Medicine, Botucatu. The diagnostic proposal of primary small cell neuroendocrine carcinoma of the mediastinum was confirmed after a detailed analysis of the organs in an autopsy examination.